Outdoor Closed System of Algal Mass Culture : In Sight of Comparison on Vertical and Horizontal Photobioreactor for Cultivating the Spirulina sp. - Hilda Farida; Puspita Sari Harahap; Rifana Sobari; Rudyanto Gunawan; Delicia Yunita Rahman; Dwi Susilaningsih (Reaktor, 2019)
Spirulina are multiceluller and filamentous blue-green algae that has gained considerable popularity in the health food industry and increasingly as a protein and vitamin supplement to aquaculture diets. The challenge for economically and fulfill the requirement for food and medical purposes has create many ways for mass-growth production, that possibly cultivated in the open-system (such as a raceway pond) or closed-system photobioreactors (such as tubular, bubble-column, airlift, flat-panel, and vertical). the cultivation of teh Spirulina on the vertical and horizontal photobioreactor has been studied. The photobioreactor, namely BJVP and BJHP, has a design to be less energy consumption using the air bubbling or circular paddle. The observation was conducted in a whole year with parameters of rainfall, temperature, light intensity, pH, and salinity. Result  showed that cultivation of Spirulina on the vertical photobioreactor growth faster than teh horizontal photobioreactor systems and the yield of biomass was about 0.94 gDW/L. Average of temperature ranges of BJHP were 31.0C-35.5C, salinities were 35 per mil level, pH were 8.55-10.86, and light intensity were 427-2001 umol photon s-1m-2. Whereas the BJVP has averages temperature range of 31.4C-33.9C, salinity 33-35 per mil level, pH 8.46-10.75, and light intensity 532-2062 umol photon s-1m-2. The proximate analyses of biomass from BJVP cultivation shows has tendency higher protein content compared to BJHP. The optimization of both reactors has continuing evaluated in order to get the optimum parameters required for economically Spirulina cultivation systems.Keywords: Spirulina, BJVP, BJHP, outdoor mass cultivating system, photobioreactor.